2006
DOI: 10.1080/02841850600644808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical 1h magnetic resonance spectroscopy of brain metastases at 1.5T and 3T

Abstract: SNR and spectral resolution were improved at higher magnetic field strength, especially with TE 144 ms, including spectra from patients with heterogeneous brain tumors. However, differences in the defined effective VOI, particularly at short echo time, reduced the expected effect of increased magnetic field strength on the measured SNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…On angiography, SNR was higher at 3 T by a factor of 1.8-2.3 [13][14][15][16]. On spectroscopy, SNR was clearly increased, although the 100 % theoretical increase was not achieved, even in phantoms, the documented increases being 23 [20], or 50 % [21]. Most gain in SNR was with short echo time spectroscopy with little improvement at long echo times [18,19,22].…”
Section: Technical Factorsmentioning
confidence: 78%
See 1 more Smart Citation
“…On angiography, SNR was higher at 3 T by a factor of 1.8-2.3 [13][14][15][16]. On spectroscopy, SNR was clearly increased, although the 100 % theoretical increase was not achieved, even in phantoms, the documented increases being 23 [20], or 50 % [21]. Most gain in SNR was with short echo time spectroscopy with little improvement at long echo times [18,19,22].…”
Section: Technical Factorsmentioning
confidence: 78%
“…Better spectral resolution at 3 T improved separation of metabolite peaks [17,18,20,21,56,57], particularly at short echo times for closely located metabolites [18,22,57], although the increase in resolution was offset by an increase in line width at 3 T [18]. No significant differences were found in metabolite ratios [22] or in whole brain N-acetylaspartate concentrations [58] between 1.5 and 3 T. Coefficients of variation for metabolite ratios and betweenexamination and subject variability were higher at 3 T for short echo time spectroscopy, but most did not reach statistical significance in one small study [17].…”
Section: Spectroscopymentioning
confidence: 99%
“…The MRI and MRS parameters have been described in previous work (29). These patients had metastases from different primary cancers: breast (patient 1), colon (patient 4) and lung (patient 13) carcinoma.…”
Section: In Vivo Mrsmentioning
confidence: 99%
“…This appears to be due to the line width increase with B 0 . Nevertheless, it is clearly demonstrated that S/N and resolution in spectra at 3 T or 7 T are improved compared to those at 1.5 T or 4 T, respectively [74][75][76][77]. Hence, higher field strength MR systems permit detecting moieties at lower concentrations, reducing resonance overlap and decreasing the voxel volume that can be observed.…”
Section: In Vivo Magnetic Resonance Spectroscopy (Mrs) Techniquesmentioning
confidence: 97%